(untitled) (Journal of Applied Oral Science, 2008)
This study evaluated the optical density of two microfilled and two microhybrid resins, as well as the composition of these materials with regard to their optical density. Cavities prepared in 12 2-mm- or 4-mm-thick acrylic plastic plates were filled with Z250 (3M-ESPE), A110 (3M-ESPE), Charisma (Heraeus-Kulzer) and DurafillVS (Heraeus-Kulzer). The resin increments (2-mm-thick) were light-cured for 40 s. Three 0.12-s radiographic exposures were made of each #2 acrylic plastic plate. DenOptix system optical plates were used to obtain the digital images. Three readings of the composite resin surface were made in each radiograph, totalizing 216 readings. The mean of highest and lowest grey-scale values was obtained. Two specimens of each composite resin were prepared for SEM analysis of the chemical elements related to optical density, using energy dispersive x-ray analysis (EDX). The results were subjected to Shapiro-Wilk's test, ANOVA, Tukey's test at 1% level of significance and Pearson's correlation. The mean grey-scale values at 2 mm and 4 mm were: Z250 = 154.27a and 185.33w; A110 = 46.77b and 63.05y; Charisma = 163.40c and 200.46z; DurafillVS = 43.92b and 58.99x, respectively. Pearson's test did not show any positive correlation between optical density and percentage weight of optical density chemical elements. It was concluded that the microhybrid resins had higher optical density means than the microfilled resins; among the evaluated resins, Charisma had the highest optical density means.